Perceptions of eating and food preparation behaviours for urban private school students in India. Issue 1 (1st January 2020) - Rathi, Neha; Riddell, Lynn; Worsley, Anthony
ABSTRACT: Introduction : Adolescents' perceptions of eating and culinary behaviours have important implications for their health and nutritional profiles. The purpose of the current investigation is to understand Indian adolescents' perceptions of healthy eating and meal preparation. Methods : Year nine students (n = 1026; 35% males) aged 14–16 years from nine English-speaking private secondary schools in Kolkata, India completed a paper-based, self-reported questionnaire which included questions about facilitators and barriers to healthy eating and meal preparation. Cross-tabulation analyses were performed to examine gender differences on the healthy eating measures. Results : Overall, the adolescents highlighted a number of key facilitators and barriers to healthy eating and meal preparation. The preference for water over sugar-sweetened beverages was cited as the most popular facilitator of healthy eating by adolescents (65.7%). The most commonly perceived barrier to healthy eating was the need for strong motivation to consume a healthy diet (56.1%). The importance of using fresh produce in food preparation (76.5%) emerged as the most prominent component of meal preparation. Conversely, the use of food lists was perceived as the least important aspect of healthy meal preparation (54.2%). In general, girls showed more positive attitudes towards healthy eating and meal preparation compared to boys. Conclusion : This understanding of Indian adolescents' perceptions of healthy eating and meal preparation suggests the development of skills-focussed nutrition education programmes to support young people in preparing and consuming healthy meals.